Ensaio de eficiência econômica e ambiental agrícola dos países componentes do BRICS - Martins, Mariana de Abreu (2022)
Globalization has mainly the countries in the form of blocks, in the area in search of productive efficiency. This dissertation focuses on investigating the technical and ecological efficiency among the countries that form the BRICS. The eco shows the performance of the ICS member countries (Brazil, Russia, India, China and South Africa) regarding the inputs and products identified the BR efficiency that may exist between the countries so that it can increase the efficiency of agriculture in the bloc . To do so, we will use the DEA-SBM Variant and Window Analysis approach. Data for inputs and outputs cover the years 2000 to 2018. The evaluation of the eco-efficiency of agriculture covers the environmental, economic and social dimensions, which may reflect the level of sustainability of agriculture in the BRICS, whose evaluation will contribute to the elaboration of policies cooperation between countries to promote sustainable agricultural development. The results presented for the analysis duration period that Russia presented the best performance for the duration period, while durability was presented in the ranking (14.3%), suggesting that it did not increase the use of its inputs to achieve a better result in your outputs the larger and undesirable.